2020
DOI: 10.3390/nu12082400
|View full text |Cite
|
Sign up to set email alerts
|

Space Flight Diet-Induced Deficiency and Response to Gravity-Free Resistive Exercise

Abstract: Immune system dysregulation is among the many adverse effects incurred by astronauts during space flights. Omega-3 fatty acids, β-alanine, and carnosine are among the many nutrients that contribute to immune system health. For space flight, crewmembers are prescribed a diet with a macronutrient composition of 55% carbohydrate, 30% fat, and 15% protein. To quantify omega-3 fatty acid, β-alanine and carnosine intakes from such a diet, and to examine each nutrient’s impact on exercise performance, 21 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Metabolomics, for example, as highlighted in this study, identified novel responses in the spleen in purine dysregulation, energy and fatty acid metabolism, which could potentially serve as substrates for countermeasure development. As common themes in responses emerge, such as in mitochondria dysfunction from animals to humans [ 56 ], it may be possible to monitor the health status of astronauts and provide corrective interventions [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics, for example, as highlighted in this study, identified novel responses in the spleen in purine dysregulation, energy and fatty acid metabolism, which could potentially serve as substrates for countermeasure development. As common themes in responses emerge, such as in mitochondria dysfunction from animals to humans [ 56 ], it may be possible to monitor the health status of astronauts and provide corrective interventions [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, regardless of the length of the expedition, space travelers should be subjected to nutritional optimization before departure. The goal is to achieve good body reservoirs, to avoid deficiencies of vitamins or minerals, and to obtain nutrition-derived immunocompetence from tailored supplements, such as omega-3 fatty acids [ 40 ]. Tailored dietary prescriptions and intake monitoring start months before launch, with astronauts being able to select their own space menu [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Summary I. A total of 13 references ([ 8 , 10 , 19 , 20 , 25 , 27 , 29 , 33 , 34 , 38 , 39 , 40 , 42 ]) were used to scope the following nutritional commonalities between pre-operative (home-based) vs. pre-launch (Earth-based) issues. The relevance of having good nutritional status; the importance to acquire nutrition-derived immunocompetence; the significance of food abstention before stressful situations; the goal of giving up/reducing bad habits; the need to opt for tailored nutrition and advanced dietary preparations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations